Transformasi Penyajian Laporan Keuangan Usaha Axmi Salon Sesuai Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) - Ni Komang Ayu Rianingsih; Ni Wayan Alit Erlina Wati; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2026)
This study transforms the presentation of Axmi Salon's financial reports in accordance with the implementation of the Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK EMKM).. The Indonesian Accounting Standards Board (DSAK) introduced the Indonesian Accounting Standards Board (DSAK) to simplify accounting guidelines for MSMEs, improve the quality of financial reporting, facilitate understanding, and minimize administrative costs. The implementation of this standard is expected to assist MSMEs in preparing complete financial reports, facilitate access to funding, and serve as a basis for business evaluation and decision-making. Axmi Salon, as an MSME in the field of care and beauty services, has not implemented a financial reporting structure in accordance with the Indonesian Accounting Standards Board (SAK EMKM), mainly because its financial records are relatively inaccurate and incomplete, covering only income and expenses. The records are still very simple and manual, do not show the correct stages of the accounting cycle, and are only understood by the owner. The purpose of this study is to determine how the transformation of the financial statement presentation model of Axmi Salon that adopts the Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The analytical method used is descriptive, comparing the financial statements applied by Axmi Salon with the Indonesian Accounting Standards Board (SAK EMKM) to identify their suitability. The results of this study indicate that the financial statement records at Axmi Salon are still very simple and not in accordance with the Indonesian Accounting Standards Board (SAK EMKM). Factors hindering the implementation of SAK MSMEs include owners' lack of understanding of accounting standards, claims that standardized record-keeping is difficult, and a lack of discipline in bookkeeping. Furthermore, there is a lack of oversight from external parties such as the government and relevant institutions.